Effect of glutamine on the blood biochemistry and the activity of serum enzymes in broilers challenged with Salmonella enteritidis - WU, Q J; LI, S W; LIU, Z H; JIAO, C; ZHU, D D; MA, Y; WANG, Y Q; WANG, Y; WU, X H (The Indian Journal of Animal Sciences, 2020)
This study was conducted to investigate the effects of glutamine (Gln) on blood biochemistry and activity of serum enzymes in broilers challenged with Salmonella enteritidis. 240 one-day-old Arbor Acres broilers were distributed into four groups treated in a completely randomized design for 21 days. The groups included a noninfection control (CON); infected with S. enteritidis (SCC); infected +0.5% Gln (Gln 1), and infected +1.0% Gln (Gln 2). The plasma total protein, albumin, and globulin concentration, AST, LDH and CK activity in SCC group were lower than the CON overall except the albumin at 14, 21 d, and CK at 14 d. SCC group had lower RBC at 7 d; lower MCHC at 14 d; higher MCHC, and MCH at 7 d, or 21 d; higher WBC at d 7, 14, and 21; higher γ-GGT activity at d 14, and 21than the CON group. Gln group had higher plasma total protein, albumin, and globulin concentration, AST, LDH and CK activity than those in SCC overall except the albumin at 14, 21 d, and CK at 14 d. Gln group had higher RBC at 7 d; higher MCHC at 14 d; lower MCHC, and MCH at 7 d, or 21 d; lower WBC at d 7, 14, and 21, and lower γ-GGT activity at d 14, and 21 than the SCC group. These results suggest that Gln could effective improve the physiological responses and maintain the normal health status of S. enteritidis infection of broilers.